Climate change mitigation initiatives in beef production systems in tropical countries - Durango, Sandra; Gaviria, Xiomara; González, Ricardo; Sotelo Cabrera, Mauricio Efren; Gutiérrez Solís, Jhon Freddy; Chirinda, Ngonidzashe; Arango, Jacobo; Barahona Rosales, Rolando (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
Cattle production in tropical countries is based on the use of extensive grazing systems, which are inefficient systems and generate low levels of profitability. Cattle production, thus, has high emissions per unit of output.